ANALISIS RISIKO KESEHATAN AKIBAT PAPARAN BENZENE MELALUI INHALASI PADA PETUGAS STASIUN PENGISIAN BAHAN BAKAR UMUM (SPBU) DI SEKITAR KAWASAN UNIVERSITAS DIPONEGORO SEMARANG - Dimas Triyadi; Nurjazuli Nurjazuli; Hanan Lanang Dangiran (Jurnal Kesehatan Masyarakat (Undip), 2016)
The use of motor vehicles increased from year to year due to seasonal residents come around Undip and area, it is impacting on the use of fuel gas stations around the area of Undip as a provider of fuel on average extension day, fill with 24,000 litres. fuel known to contain organic compounds, namely benzene that is dangerous on gas station attendant.This research aims to know the level of health risk due to exposure to benzene through inhalation on the gas station in the area around the Diponegoro University of Semarang. This research population is 78 people from 4 gas station. The number of samples obtained with the formula slovin of 28 people. This research is descriptive research that uses a risk assessment approach to environmental health. Data obtained from the measurement of the concentration of benzene inhaled aerial, weight measurements, interviews, and the study of literature. The results of measurement of concentrations of benzene aerial is of 28 respondents, respondents 1 threshold value exceeds 0,5 ppm specified Permenakertrans RI No.13 Tahun 2011 of 2,0791 ppm. The analysis to the data by doing the calculations benzene intake. The resulting intake values are then compared to the Reference Concentration (RfC) for non carcinogens effects and Cancer Slope Factor (CSF) for the effects of carcinogens. Analysis of the result obtained for the effects of non carcinogens realtime, namely RQ ≤ 1 is 71,4%, RQ > 1 is 28,6%, and effect of non carcinogens lifetime, namely RQ ≤ 1 is 10,7%, RQ > 1 is 89,3%. While the effects of carcinogens realtime, namely on ECR ≤ 10-4 is 39,3%, on ECR > 10-4 is 60,7% and effects of carcinogens,namely ECR >10-4 is 100%. In conclusion, the level of non carcinogens health risks mostly secured or not yet at risk and the level of carcinogens health risk mostly unsafe or risky.